2006
DOI: 10.1038/sj.ki.5000447
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk for patients receiving hemodiafiltration versus hemodialysis: European results from the DOPPS

Abstract: Hemodiafiltration (HDF) is used sporadically for renal replacement therapy in Europe but not in the US. Characteristics and outcomes were compared for patients receiving HDF versus hemodialysis (HD) in five European countries in the Dialysis Outcomes and Practice Patterns Study. The study followed 2165 patients from 1998 to 2001, stratified into four groups: low- and high-flux HD, and low- and high-efficiency HDF. Patient characteristics including age, sex, 14 comorbid conditions, and time on dialysis were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
273
2
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(297 citation statements)
references
References 54 publications
8
273
2
14
Order By: Relevance
“…Actually, lower predialysis ␤2M levels have been reported after 3 to 12 mo treatment with HDF, as compared with low-flux or high-flux HD (10)(11)(12)(13)(14)(15). It has been proposed that the improved survival of HDF patients, as reported in few observational studies (16)(17)(18), can be partly attributed to increased removal of ␤2M and other MMW uremic toxins by convective transport.…”
mentioning
confidence: 92%
“…Actually, lower predialysis ␤2M levels have been reported after 3 to 12 mo treatment with HDF, as compared with low-flux or high-flux HD (10)(11)(12)(13)(14)(15). It has been proposed that the improved survival of HDF patients, as reported in few observational studies (16)(17)(18), can be partly attributed to increased removal of ␤2M and other MMW uremic toxins by convective transport.…”
mentioning
confidence: 92%
“…In this study, the risk of mortality was significantly reduced when the duration of the dialysis session exceeded 4 h; each 30 min extension of dialysis reduced the mortality risk by about 7 % [18].…”
Section: Introductionmentioning
confidence: 51%
“…In addition, DOPPS has also shown that overall clinical practices at the facility level were essential for improving patient outcomes [21]. In other words, dialysis facilities achieving optimal targets for a core of selected quality control items in the majority of patients were extending life expectancy to each patient individually [ 21 ]). In this new perspective, it is then necessary to implement complementary items of quality control probing the degree of compliance of dialysis facilities with best clinical practices [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the main findings of DOPPS it must be stressed that less use of central venous catheter [10,11], longer duration of dialysis with reduced ultrafiltration rate [12], adequate dialysis schedule [13], higher dialysis dose delivered [14], better control of fluid overload and blood pressure control [15], prevention of metabolic bone disease [16,17], better control of anaemia with lower erythropoiesis-stimulating agent dose require-ment [18,19], enhanced convective dose [20] are all beneficial to patient outcomes. In addition, DOPPS has also shown that overall clinical practices at the facility level were essential for improving patient outcomes [21]. In other words, dialysis facilities achieving optimal targets for a core of selected quality control items in the majority of patients were extending life expectancy to each patient individually [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%